Gender-based violence: the case of the Fluminense Federal University - Freitas, Rita de Cássia Santos; Musmanno Gonçalves, Rafaella; de Souza Carvalho, Monique (Argumentum, 2020)
This article presents reflections on the results obtained through the research “Observatory of Gender-based Violence - Analyzing the Federal Fluminense University”, which aimed to analyze gender-based violence on the different campuses of this university, in addition to capturing the degree of knowledge of different subjects about this phenomenon and their coping network. Through the use of research methods of bibliographic review and analysis of qualitative and quantitative data, the data collected from UFF students, staff, and teachers were examined. The article focuses on the results of this research, which was discontinued, but that sustains its scientific validity by contributing to the intensification of the discussion of gender-based and the construction of public policies in this context, although without a pretense of generalized analysis.Keywords: Gender-based violence. Violence against women. LGBTI+phobia. University. Intersectionalities.